Numerical Analysis of Thorax Injury Caused by the Blunt Impact of SIR-X Sponge Grenade - Chen, Chaoming; Zhao, Fadong; Ma, Zongmin (Human factors and mechanical engineering for defense and safety, 2023)
To effectively assess the injury risk of the blunt impact of the SIR-X sponge grenade on the human thorax, in this paper, we used a numerical simulation technique to test the non-lethal kinetic energy projectiles that blunt impact on the Hybrid III 50th dummy model. By simulating the effect of the L5 projectile on the thorax of the Hybrid III 50th dummy model, about NATO standard AEP-99 (2021 edition), the thoracic displacement curves of the dummy model in three testing conditions were obtained in the validation corridors. The idea of replacing the finite element model of the human body with the Hybrid III 50th dummy finite element model was proposed. We considered the difficulty in obtaining data due to the large deformation of the contact position when the SIR-X sponge grenade impacts the dummy’s thorax. We proposed a mathematical model to predict the impact injury of the human thorax using the rib displacement measured by the rib displacement sensor of the Hybrid III 50th dummy. We simulated the SIR-X sponge grenade blunt impacting the dummy model’s thorax. The measured rib displacement was used to predict and analyze the injury risk of the human thorax, providing a specific data reference for practical application.